Transfusion of recently donated (fresh) red blood cells (RBCs) does not improve survival in comparison with current practice, while safety of the oldest stored units is yet to be established: a meta‐analysis. Issue 1 (5th February 2016) - Remy, K. E.; Sun, J.; Wang, D.; Welsh, J.; Solomon, S. B.; Klein, H. G.; Natanson, C.; Cortés‐Puch, I.
Abstract : Background and Objectives: Preclinical studies generated the hypothesis that older stored red blood cells (RBCs) can increase transfusion risks. To examine the most updated and complete clinical evidence and compare results between two trial designs, we assessed both observational studies and randomized controlled trials (RCTs) studying the effect of RBC storage age on mortality. Materials and Methods: Five databases were searched through December 2014 for studies comparing mortality using transfused RBCs having longer and shorter storage times. Results: Analysis of six RCTs found no significant differences in survival comparing current practice (average storage age of 2 to 3 weeks) to transfusion of 1‐ to 10‐day‐old RBCs (OR 0·91, 95% CI 0·77‐1·07). RBC storage age was lower in RCTs vs. observational studies ( P  = 0·01). The 31 observational studies found an increased risk of death (OR 1·13, 95% CI 1·03–1·24) ( P  = 0·01) with increasing age of RBCs, a different mortality effect than RCTs ( P  = 0·02). Conclusion: RCTs established that transfusion of 1‐ to 10‐day‐old stored RBCs is not superior to current practice. The apparent discrepancy in mortality between analyses of RCTs and observational studies may in part relate to differences in hypotheses tested and ages of stored RBCs studied. Further trials investigating 1‐ to 10‐day‐old stored RBC benefits would seem of lower priority than studies to determine whether 4‐ to 6‐week stored units have safety and efficacy equivalent to the 2‐ to 3‐week‐old stored RBCs commonly transfused today.